2022
DOI: 10.1021/acssuschemeng.1c07176
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Seawater-Degradable Poly(butylene succinate-l-lactide) Copolyesters: Exploration of Degradation Performance and Degradation Mechanism in Natural Seawater

Abstract: In view of the problem of marine plastic pollution and oil resource depletion, an innovative attempt was made to obtain biobased seawater-degradable polyesters by installing lactic acid (LA) into the poly(butylene succinate) (PBS) backbone and synthesizing a series of random copolyesters named poly(butylene succinate-L-lactide)s (PBSLs). Herein, biobased LA units are chosen as readily hydrolyzable points according to our theoretical calculation. The obtained PBSL copolyesters preserve the structure of PBS when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…At the same time, from the released final degradation product CO 2 curve in the seawater degradation experiment, it can be observed that the mineralization rate of PBSG, compared with cellulose, is extremely slow in the first 100 days, which means that PBSG is in the incubation period for a long time during the entire degradation process, existing in the form of microplastics of low molecular weight polymers 44 . Similarly, the same degradation process is exhibited in PBSL copolyester, showing the limitation of seawater‐degradable materials obtained by this kind of copolymerization modification 47 …”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…At the same time, from the released final degradation product CO 2 curve in the seawater degradation experiment, it can be observed that the mineralization rate of PBSG, compared with cellulose, is extremely slow in the first 100 days, which means that PBSG is in the incubation period for a long time during the entire degradation process, existing in the form of microplastics of low molecular weight polymers 44 . Similarly, the same degradation process is exhibited in PBSL copolyester, showing the limitation of seawater‐degradable materials obtained by this kind of copolymerization modification 47 …”
Section: Introductionsupporting
confidence: 60%
“…44 Similarly, the same degradation process is exhibited in PBSL copolyester, showing the limitation of seawater-degradable materials obtained by this kind of copolymerization modification. 47 In the background of advocating the reduction and absence of microplastics, the original intention of the design of seawater-degradable materials should be to make the materials "disappear" as soon as possible after being discarded into seawater. Shortening the period for materials to degrade into final products represents reducing the amount of material entering the natural environment, resulting in a better environmental footprint than existing conventional plastics.…”
Section: Introductionmentioning
confidence: 99%
“…Polyamides, which have repeated amide bonds and carbon linkages in the main chain, are one of the most widely used synthetic polymers in structural materials such as fibers for fabrics and fishing nets and industrial membranes due to their excellent mechanical and thermal properties. Since amide bonds can be hydrolyzed in the presence of water molecules, polyamides are considered to be a promising (bio)­degradable material. However, degradation is generally slower for polyamides than for other degradable polymers such as polyesters due to the strong intermolecular interactions and stable resonance structure in their chains . In fact, it has been reported that the most commercially used polyamide polymers such as polyamide 6 (PA6) and polyamide 66 are well decomposed only in some specific microorganism environments but not under marine conditions. …”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic polyesters play an increasingly important role in environmental and biomedical applications due to their remarkable biodegradability and biocompatibility. Current major research centers on the development of saturated aliphatic polyesters, such as polylactide, poly­(butylene succinate), and polyglycolide. However, this type of polyester suffers from an inherent drawback that lacks reactive groups along the backbones, thereby limiting its applicability and further functionalization. In this context, unsaturated polyesters (UP) have attracted more and more interest since they can be easily tailor-made to achieve the requested properties. , The special unsaturated bond can not only act as reactive sites toward chemical modification but also render UP with unique crystalline structures and physical properties.…”
Section: Introductionmentioning
confidence: 99%